Political Differences in Past, Present, and Future Life Satisfaction: Republicans Are More Sensitive than Democrats to Political Climate - Mandel, David R. (Public Library of Science, 2014)
Previous research finds that Republicans report being happier or more satisfied with their lives than Democrats. Using representative American samples from 2002, 2005, 2007, 2009, and 2010, we tested a Person × Situation interactionist account in which political affiliation (Democrat, Republican) and political climate (favorable when the president in office is of the same party) are proposed to affect past, present, and anticipated future life satisfaction. Meta-analyses of related tests of key hypotheses confirmed that (a) life satisfaction was greater when the political climate was favorable rather than unfavorable and (b) Republicans were more sensitive to political climate than Democrats. As predicted, Republicans also were more politically polarized than Democrats. Taken together, the findings indicate that, compared to Democrats, Republicans are more apt to self-identify in political terms, and core aspects of their subjective well-being are more easily affected by the outcome of political events.